Generalizing About Striking Properties: Do Glippets Love to Play With Fire? - Lazaridou-Chatzigoga, Dimitra; Katsos, Napoleon; Stockall, Linnaea (Frontiers in Psychology, 2019)
Two experiments investigated whether 4- and 5-year-old children are sensitive to whether the content of a generalization is about a salient or noteworthy property (henceforth “striking”) and whether varying the number of exceptions has any effect on children’s willingness to extend a property after having heard a generalization. Moreover, they investigated how the content of a generalization interacts with exception tolerance. Adult data were collected for comparison. We used generalizations to describe novel kinds (e.g., “glippets”) that had either a neutral (e.g., “play with toys”) or a striking property (e.g., “play with fire”) and measured how willing participants were to extend the property to a new instance of the novel kind. Experiment 1 demonstrated that both adults and children show sensitivity to strikingness in that striking properties were extended less than neutral ones, although children extended less than adults overall. The responses of both age groups were significantly different from chance. Experiment 2 introduced varying numbers of exceptions to the generalization made (minimal: 1 exception; maximal: 3 exceptions). Both adults and children extended both types of properties even in the face of exceptions, but to a lower degree than in Experiment 1. Striking properties were extended less than neutral ones, as in Experiment 1. We observed that the greater the number of exceptions, the lower the rates of extension we obtained, for both types of properties in adults, but only with striking properties in children. Children seemed to keep track of varying numbers of exceptions for striking properties, but their performance did not differ from chance. The findings underscore that 4- and 5-year-old children are sensitive to strikingness and to exception tolerance for generalizations and are developing toward an adult-like behavior with respect to the interplay between strikingness and exception tolerance when they learn about novel kinds. We discuss the implications of these results with regards to how children make generalizations.